ISOLASI DAN IDENTIFIKASI SENYAWA TRITERPENOID DARI EKSTRAK n-HEKSAN FRAKSI 8 NODA KE- 2 DARI DAUN MERAH PUCUK MERAH (Syzygium Myrtifolium Walp.) - Septi Roro Liniawati; Chairul Saleh; Erwin Erwin (JURNAL KIMIA MULAWARMAN, 2019)
Isolation and identification of triterpenoid componds n-hexsane extract on 8 fraction of second stain from red leaf of Pucuk Merah (Syzygium myrtifolium Walp.) leaves has done. The leaves red Pucuk Merah has potential as bioactive ingredients of traditional medicinal plants in Indonesia. These leaves contain secondary metabolites Triterpenoid which has been tested phytochemical and bioactivity as antibacterial and antioxidant. Isolation was conducted by maceration method with ethanol, ethanol extract was partition with n-Hexane solvent. Then proceed with the separation by column chromatography isocratic. The results of the isolation process which isolates obtained second fractions 8 as white powder to 1.2 mg with Rf value of 0.625. Based on GC-MS analysis showed four major compounds contained in n-hexane fraction red Pucuk Merah leaves namely cis-6-ethyl-4a-cis, trans-8a-perhydro-trans-1-2-methoxycarbonylethyl)-trans-2,tr; phthalic acid, di (2-propylpentyl) ester; benzenesulfonanilide; and 14-Î²-H-Pregnan with a molecular weight of 339; 390 ; 233 and 288